THE ROLE OF INDIGENOUS KNOWLEDGE IN SUSTAINABLE FOREST MANAGEMENT - Aung, Hnin Thiri; Hlaing, Nandar; Lin, Tun (Yayasan Adra Karima Hubbi, 2025)
Indigenous knowledge has long been a cornerstone in the management of natural resources, particularly in the sustainable use and conservation of forests. With increasing pressure on forests due to climate change and human activities, there is a growing interest in integrating indigenous practices with modern forest management strategies. Despite its significance, the role of indigenous knowledge in promoting sustainable forest management (SFM) remains underexplored in contemporary research. This study aims to explore the contributions of indigenous knowledge to sustainable forest management practices, particularly in the context of biodiversity conservation, forest regeneration, and the resilience of forest ecosystems. The research focuses on identifying how traditional ecological knowledge can complement scientific forest management techniques to foster more effective and culturally appropriate solutions to forest conservation. A qualitative research approach was used, employing semi-structured interviews and focus group discussions with indigenous communities in forested regions. Secondary data from government reports and local conservation organizations were also analyzed. The study was conducted in three distinct forest regions, each with a different indigenous culture and forest management tradition. The study found that indigenous knowledge systems contribute significantly to the maintenance of biodiversity, the prevention of deforestation, and the sustainable harvesting of forest resources. Traditional practices such as rotational farming, sacred groves, and community-based monitoring systems play a crucial role in preserving forest ecosystems and ensuring their long-term health. Indigenous knowledge is an invaluable resource in the effort to achieve sustainable forest management. The integration of traditional ecological practices with modern conservation strategies can enhance the effectiveness of forest management, promoting both ecological sustainability and community well-being.